2020
DOI: 10.1111/jpm.12670
|View full text |Cite
|
Sign up to set email alerts
|

Men’s experiences of eating disorder treatment: A qualitative systematic review of men‐only studies

Abstract: Accessible summary What is known on the subject? There is a widespread perception that eating disorders are predominantly women´s illnesses. Most studies in the field of eating disorders include predominantly women. Current eating disorder programmes are tailored to meet women´s needs. At the same time, studies show that the rate of eating disorders among men is rising. Men tend to seek help for their eating disorder late in the course of their illness; even when they do seek treatment, they run risk of bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Most of the included systematic reviews concerned both women and men with EDs, but men were underrepresented relative to their expected incidence, which possibly reflects the proportions of women and men that are studied in the primary qualitative studies of EDs. This is confirmed by a recent systematic review on men’s experiences of ED treatment[ 42 ], which identified only nine primary studies (not included in this review since it was published after our literature search). Since the prevalence of EDs is known to be higher among women, there might be a tendency to overlook the problem in men and boys.…”
Section: Discussionsupporting
confidence: 67%
“…Most of the included systematic reviews concerned both women and men with EDs, but men were underrepresented relative to their expected incidence, which possibly reflects the proportions of women and men that are studied in the primary qualitative studies of EDs. This is confirmed by a recent systematic review on men’s experiences of ED treatment[ 42 ], which identified only nine primary studies (not included in this review since it was published after our literature search). Since the prevalence of EDs is known to be higher among women, there might be a tendency to overlook the problem in men and boys.…”
Section: Discussionsupporting
confidence: 67%
“…No group differences in duration of illness emerged in the current study. Some studies have highlighted that males with eating disorders report delayed recognition of the eating disorder and difficulties accessing treatment [ 41 ]. Males are also more likely to have an undiagnosed eating disorder, which has been attributed to perceived stigma and reluctance to seek treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…No group differences in duration of illness emerged in the current study. Some studies have highlighted that males with eating disorders report delayed recognition of the eating disorder and difficulties accessing treatment (Richardson & Paslakis, 2021). Males are also more likely to have an undiagnosed eating disorder, which has been attributed to perceived stigma and reluctance to seek treatment (Griffiths et al, 2015).…”
Section: Discussionmentioning
confidence: 99%